The University of Michigan Dioxin Exposure Study: Population Survey Results and Serum Concentrations for Polychlorinated Dioxins, Furans, and Biphenyls - Hedgeman, Elizabeth; Chen, Qixuan; Hong, Biling; Chang, Chiung-Wen; Olson, Kristen; LaDronka, Kathleen; Ward, Barbara; Adriaens, Peter; Demond, Avery; Gillespie, Brenda W.; Lepkowski, James; Franzblau, Alfred; et al. (Environmental health perspectives, 2009)
Background: The University of Michigan Dioxin Exposure Study was undertaken to address concerns that the discharge of polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) from the Dow Chemical Company in the Midland, Michigan, area had resulted in contamination of soils in the Tittabawassee River floodplain and the city of Midland, leading to an increase in residents' body burdens of these compounds. Objective: In this article we present descriptive statistics from the resident survey and sampling of human serum, household dust, and soil and compare them with other published values. Methods: From a multistage random sample of populations in four areas of Midland and Saginaw counties and from a distant referent population, we interviewed 946 adults, who also donated blood for analysis of PCDDs, PCDFs, and polychlorinated biphenyls (PCBs). Samples of household dust and house perimeter soil were collected from consenting subjects who owned their property. Results: All five study populations were comparable in age, race, sex, and length of residence in their current home. Regional differences existed in employment history, personal contact with contaminated soils, and consumption of fish and game from contaminated areas. Median soil concentrations were significantly increased around homes in the Tittabawassee River floodplain (11.4 ppt) and within the city of Midland (58.2 ppt) compared with the referent population (3.6 ppt). Median serum toxic equivalencies were significantly increased in people who lived in the floodplain (23.2 ppt) compared with the referent population (18.5 ppt). Conclusions: Differences in serum dioxin concentrations among the populations were small but statistically significant. Regression modeling is needed to identify whether the serum concentrations of PCDDs, PCDFs, and PCBs are associated with contaminated soils, household dust, and other factors.